Falling Back in Love with Trans-Inclusive Feminism: Canadian Creative Artists Re-Story Death and Choose Transformation - Devon Harvey (Humanities)
Prevailing political and popular narratives often treat the issue of trans death as an inevitability and reduce complex stories of trans life to their endings. This paper investigates the transformative potential of creative forms of resistance—specifically a selection of Canadian poetry, personal essays, and comics—and how their artistic affordances engage with transfeminism as an approach to narratives of trans existence. Rooted in Canadian author Kai Cheng Thom’s reckoning with the shortcomings of trans-exclusionary feminist thought, and informed by Chinua Achebe’s conceptualization of re-storying, this article explores how I Hope We Choose Love and Falling Back in Love with Being Human by Kai Cheng Thom, Death Threat by Canadian creatives Vivek Shraya and Ness Lee, and comics from Assigned Male by trans activist and Canadian comic artist Sophie Labelle re-story “necessary” trans death to orient queer death spaces around a trans-for-trans (t4t) praxis of narrativization. Addressing the (inter)disciplinary possibilities of trans-inclusive feminism and comics studies, this article celebrates how these texts disavow and re-story the “Good” Trans Character, who dies to satisfy transmisogynistic ideologies, and theorizes the T4t Dead Trans Character, who dies to reclaim instances of trans death and recodify trans personhood as a site of hope, agency, and self-determination. In their re-storying, these texts recognize the transformative potential of trans existence and echo Thom in their urging of trans-inclusive feminism to renounce narratives of disposability and invest in the dignity of all human life.